EPCT-02. COMPARISON OF TARGETED AGENTS RECOMMENDED BY THE CNS-TAP TOOL TO THOSE SELECTED BY A TUMOR BOARD IN A MOLECULARLY-DRIVEN DIPG CLINICAL TRIAL - Roberts, Holly (Neuro Oncol, 2021)
Recently, sequencing of diffuse intrinsic pontine glioma (DIPG) biopsy specimens has revealed genomic heterogeneity of these tumors, fueling an interest in individualized, targeted treatment options. The Pacific Pediatric Neuro-Oncology Consortium recently completed enrollment onto a feasibility study PNOC003: Molecular Profiling for Individualized Treatment Plan for DIPG (NCT02274987), in which a multidisciplinary tumor board recommended molecularly-targeted agents based on genomic and molecular profiling of each patient’s tumor. Separately, our group developed the Central Nervous System Targeted Agent Prediction (CNS-TAP) tool, which combines pre-clinical, clinical, and CNS penetration data with patient-specific genomic information to allow for numeric scoring of targeted anticancer agents to objectively evaluate these therapies for use in patients with CNS tumors. We hypothesized that highly-scored agents within CNS-TAP would overlap with the agents recommended by the tumor board in this study. For each PNOC003 participant, we utilized the genomic report to identify actionable alterations and input patient-specific data into CNS-TAP to identify the highest scoring agents. We compared high-scoring agents within CNS-TAP with recommendations from the PNOC003 tumor board for each of the enrolled 28 subjects. Overall, 93% (26/28) of patients had at least one agent recommended by both the tumor board and CNS-TAP. Additionally, 38% (37/95) of all agents recommended by the tumor board were also selected by CNS-TAP. Furthermore, we identified factors that likely contributed to the discordance between these two methods. Without clinician input, CNS-TAP is unable to account for drug-drug interactions, includes only designated anticancer agents, and cannot easily be updated in real time. However, CNS-TAP provides an objective evaluation of targeted therapies, whereas tumor boards are inherently subjective. Given the discordance identified between these methods and the strengths of each, a prospective study incorporating both CNS-TAP and a molecular tumor board for targeted therapy selection in DIPG patients is warranted.